(untitled) (Revista Iberoamericana de Bioética, 2020)
Recent decades have seen a progressive ageing of the population that is drawing the attention of institutions worldwide in order to promote healthy ageing. Chronic diseases are part of ageing and the geriatric population is the largest consumer of drugs. Limiting the participation of this population in clinical research may result in a lack of information on drug safety and efficiency. It is necessary to take actions that include clinical research as part of healthy ageing as it promotes active ageing and provides relevant information for better use of medicines within this sector of the population.